EMG Signal Analysis Of Fatigue Muscle Activity In Manual Lifting - Tengku Zawawi , Tengku Nor Shuhada; Abdullah, Abdul Rahim; Shair, Ezreen Farina; Halim, Isa; Mohamad Saleh, Saleha (Engineering and Scientific Research Groups, 2015)
-